Factors associated with outcomes of second-line treatment for EGFR-mutant non-small-cell lung cancer patients after progression on first- or second-generation EGFR-tyrosine kinase inhibitor treatment - Chang, Cheng-Yu; Chen, Chung-Yu; Chang, Shih-Chieh; Chen, Ching-Yi; Lai, Yi-Chun; Chang, Chun-Fu; Wei, Yu-Feng (Frontiers in Oncology, 2023)
Purpose: Epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) are standard first-line treatments for advanced EGFR-mutant non-small-cell lung cancer (NSCLC) patients. However, factors associated with outcomes after progression on first-line therapy are seldom investigated. Materials and Methods: From January 2016 to December 2020, we enrolled 242 EGFR-mutant stage IIIB–IV NSCLC patients who progressed on first- or second-generation EGFR-TKI treatments, and 206 of them receive second-line treatments after disease progression. The factors that predict the survival outcomes of different second-line treatments after disease progression were evaluated. Clinical and demographic characteristics, including metastatic sites, neutrophil-to-lymphocyte ratio (NLR) at first-line progression, and second-line treatment regimens, and whether re-biopsied after disease progression or not, were reviewed for outcome analysis. Results: The univariate analysis showed that the PFS was shorted in male patients (p =0.049), patients with ECOG performance state ≥ 2 (p =0.014), former smokers (p =0.003), patients with brain metastasis (p =0.04), second-line chemotherapy or EGFR-TKIs other than osimertinib (p =0.002), and NLR ≥5.0 (p=0.024). In addition, second-line osimertinib was associated with longer OS compared to chemotherapy and other EGFR-TKI treatment (p =0.001). In the multivariate analysis, only second-line osimertinib was an independent predictor of PFS (p =0.023). Re-biopsy after first-line treatment was associated with a trend of better OS. Patients with NLR ≥5.0 at disease progression had shorter OS than patients with NLR <5.0 (p = 0.008). Conclusion: The benefits of osimertinib necessitate that aggressive re-biopsy after progression on first- or second-generation EGFR-TKI treatment is merited for appropriate second-line treatments to provide better outcomes for these patients.